Manajemen Susut PT. PLN (Persero) Rayon Siak Dengan Menggunakan Metode Perhitungan Rumus Susut Jogja - Ainur Rohmah; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
As solely company to manages electricity in Indonesia PT. PLN (Persero) often suffer from business loss due to the following reason, i.e. vulnerability power, unsecure risk, improper finance cost, unknown billing target for street’s lighting. To anticipate those problem PLN has conducted best practice in term of losses management which known by Rumus Susut Jogja. This paper proposed this method for PT. PLN (Persero) Rayon Siak to overcome above mentioned problems. Rumus Susut Jogja method has several mechanisms to perform analysis. Firstly, collect the data assets, production’s data, and selling’s data according to the unit’s condition. Then, the process continue by Rumus Susut Jogja to get each losses value. The result of Rumus Susut Jogja was presented in Chart Dupont which divide losses into two part, i.e. technical losses and non-technical losses, so we can evaluate and analyst the losses. Based on the data calculation, PLN Rayon Siak on February 2016 shows the high range losses still remain with 11,59% total losses. This value is approaching the value that showed by [Khord, H.M., et.al.,2002]. Overalls, Rumus Susut Jogja has proven for PLN Rayon Siak able to obtained the exact value of total losses line distribution and successfully to achieve the target into 7,35% by December 2016.Keywords: losses, calculation method, rumus susut jogja